OP0086 Alterations of immune cellular circadian rhythms in rheumatoid arthritis. (23rd January 2014) - Spies, C.M.; Gaber, T.; Hoff, P.; Mazuch, J.; Maier, B.; Hahne, M.; Strehl, C.; Tran, C.L.; Soboleva, N.; Stoehr, A.; Wagegg, M.; Fangradt, M.; et al.
Abstract : Background: The circadian variation of clinical symptoms and the underlying variation of cytokine and hormone levels in rheumatoid arthritis (RA) are well described and have already led to the successful application of chronotherapy with prednisone (Buttgereit et al., Lancet, 2008). Much less is known about the circadian rhythms of different immune cell populations in RA. Objectives: In this pilot study we investigated molecular, cellular and humoral circadian parameters in postmenopausal female RA patients in comparison to healthy control subjects. Methods: Blood samples from postmenopausal female patients with active RA (DAS 28 ≥4.2) (n=5) and postmenopausal female healthy controls (n=5) were collected every 2 hours for 24 hours and analysed by flow cytometry and multiplex suspension array of 28 cytokines. Clock gene expression of isolated CD14+ monocytes was analysed by quantitative RT-PCR. Endogenous circadian rhythm dynamics of macrophages were determined by means of a Bmal1 -promotor driven luciferase reporter construct. COSINOR analysis was used for statistical analysis of the groups. Results: Expression of the clock gene RevErbα in CD14+ monocytes showed a significant circadian expression pattern in both RA patients and healthy controls subjects, whereas the clock genes Per2 and Per3 were not expressed in a circadian manner in RA patients but in healthy controls only. The amplitude of the endogenous circadian rhythm of macrophages tended to be lower in RA patients than in healthy controls, whereas period length was not altered. In flow cytometric analysis of surface marker expression of blood cells we found a significant circadian rhythm in RA patients and healthy subjects for the frequency of CD3-CD56+ natural killer (NK) cells, Interleukin-8 Receptor (IL-8R) expressing CD4+ T helper and CD8+ cytotoxic T cells, and CXCR4 expressing CD4+ T helper and CD8+ cytotoxic cells . A significant circadian rhythm was not detectable in RA patients but in healthy controls only for CD3+CD56+ NK T cells . In contrast, a significant circadian expression of IL-8R+ monocytes was found in RA patients only but not in healthy subjects. Of note, CCR7 did not at all show a circadian expression. A significant circadian cytokine expression was detected only for MCP-1 in healthy controls. Conclusions: This is the first indication of alterations of clock gene expression and endogenous circadian rhythms in immune cells of RA patients. Traffic of peripheral blood cells shows circadian variation in RA patients and healthy controls with characteristic peak phases, especially in NK cells and chemokine receptor expressing cells. NKT and other cells may lose their normal circadian rhythm in RA, whereas IL-8R expression on monocytes may be established as new "inflammatory" circadian rhythm in RA patients. These findings provide new aspects of RA chronobiology and may have therapeutic implications. Disclosure of Interest: C. Spies: None Declared, T. Gaber: None Declared, P. Hoff: None Declared, J. Mazuch: None Declared, B. Maier: None Declared, M. Hahne: None Declared, C. Strehl: None Declared, C. Tran: None Declared, N. Soboleva: None Declared, A. Stoehr: None Declared, M. Wagegg: None Declared, M. Fangradt: None Declared, M. Jakstadt: None Declared, D. Huscher: None Declared, G.-R. Burmester: None Declared, J. Detert: None Declared, A. Kramer: None Declared, F. Buttgereit Grant/Research support from: This study was supported by Horizon Pharma AG, Reinach, Switzerland and Merck KGaA, Darmstadt, Germany. Dr. Buttgereit reports receiving consultancy fees, honoraria and travel expenses from Merck Serono, Horizon Pharma (formerly Nitec Pharma) Mundipharma Int Ltd and grant support from Merck Serono and Horizon Pharma., Consultant for: see above, Speakers Bureau: see above